2019
DOI: 10.3892/ol.2019.10657
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog pathway mediates genistein inhibition of renal cancer stem cells

Abstract: Cancer stem cells (CSCs) have been implicated in the genesis, progression and recurrence of renal cancer. The sonic hedgehog (Shh) pathway serves a critical role in maintaining the stemness of CSCs. Genistein, a major isoflavone component extracted from soybeans and soy products, has been demonstrated to possess anticancer activity. However, the effects of genistein on renal CSCs and its underlying mechanisms remain to be fully elucidated. The aim of the present study was to investigate the role of the Shh pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…An in vitro study investigating the role of the Shh signaling pathway in the anticancer inhibitory effect of genistein showed that genistein targeted cancer stem cells in malignant tumors, and significantly reduced the number and size of kidney cancer stem cells in a dose-dependent manner. In addition, genistein had an effect on cell proliferation and apoptosis and dose-dependently decreased the expression levels of the Shh pathwayrelated proteins (Table S6) [182]. These results show that genistein has an inhibitory effect on renal cancer stem cells by inhibiting the Shh signaling pathway.…”
Section: Anticarcinogenic Activity Through Gene Regulationmentioning
confidence: 66%
“…An in vitro study investigating the role of the Shh signaling pathway in the anticancer inhibitory effect of genistein showed that genistein targeted cancer stem cells in malignant tumors, and significantly reduced the number and size of kidney cancer stem cells in a dose-dependent manner. In addition, genistein had an effect on cell proliferation and apoptosis and dose-dependently decreased the expression levels of the Shh pathwayrelated proteins (Table S6) [182]. These results show that genistein has an inhibitory effect on renal cancer stem cells by inhibiting the Shh signaling pathway.…”
Section: Anticarcinogenic Activity Through Gene Regulationmentioning
confidence: 66%
“…In addition, cleaved PARP is an indicator of apoptosis. An increased expression of PARP has been observed in several tumor types and has been linked to drug resistance and increased survival of genotoxic stress (141-145) as well as the promotion and maintenance of cancer stemness (146)(147)(148)(149). In some animal studies, PARP has also been linked to the survival response after photon radiation exposure, since the use of a PARP inhibitor in combination with photon radiation was able to enhance the effect of photon radiation, by decreasing cell growth and cell survival (150)(151)(152)(153).…”
Section: Dna Damage Signaling Involving Poly(adp-ribose) Polymerase (mentioning
confidence: 99%
“…Isoflavones derived from soy, such as genistein, have been established to have significant anti-cancer effects against leukemia, lymphoma, gastric, breast, prostate and non-small cell lung cancer [44]. Several studies have reported the anti-cancer effects of genistein in various cancer models such as prostate cancer [108], breast cancer [109], lung cancer [110] and head and neck squamous cell carcinoma [111], cervical cancer [112], ovarian cancer [113], renal cancer [114], bladder cancer [115], liver cancer [116] as shown in Table 1. Induction of apoptosis by genistein treatment was shown through inhibition of IGF-1R/p-Akt signaling in breast cancer [43].…”
Section: Isoflavonesmentioning
confidence: 99%